Technology is not gender neutral - Factors that influence agricultural technology adoption by men and women - Flores, Paola (International Potato Center, 2018)
Presented by Paola Flores (CIP), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.